Effect of Formulation with Papaya Sauce as Fat Replacer on Butter Cake Texture - Ang, Eng May; Abdullah, Norazlin; Muhammad, Norhayati; Lizardo, Rona Camille M. (Journal of Science and Technology, 2017)
Fat helps to provide better creaminess, appearance, flavour and texture in food. However, excessive intake of fats may cause obesity, coronary heart disease, high blood cholesterol and diabetes. Fat replacer may help reduce the fat content in food while retaining the sensory properties because it has some or same function as fat. The aim of this research was to investigate the effect of ingredient formulation with papaya sauce as fat replacer in butter cake. Amounts of butter, fresh milk, and papaya sauce were the independent variables. Papaya was chosen as a fat replacer due to the presence of pectin. The dependent variables were firmness and fat content of the cake. Cake slices with 25 mm Ã— 25 mm Ã— 25 mm dimensions were prepared after the cake cooled for one hour at room temperature. It was observed that by varying substitution level of papaya sauce in the formulation, the texture of the cake was affected. The texture profile analysis of butter cakes showed that the cakes become softer with increasing amount of papaya sauce and decreasing amount of milk in the formulation. The replacement of fat by substituting with other ingredient affected the gluten development in cake that in turn influenced the texture. Hence, it is concluded that increasing substitution of papaya sauce affects the firmness of cake.